International conference on advancements of medicine and health care through technology; 5th - 7th June 2014, Cluj-Napoca, Romania : MEDITECH 2014 - Ciupa, Radu V.; Vlad, Simona (IFMBE Proceedings, 2014)
This volume presents the contributions of the third International Conference on Advancements of Medicine and Health Care through Technology (Meditech 2014), held in Cluj-Napoka, Romania. The papers of this Proceedings volume present new developments in - Health Care Technology, - Medical Devices, Measurement and Instrumentation, - Medical Imaging, Image and Signal Processing, - Modeling and Simulation, - Molecular Bioengineering, - Biomechanics.